Internalisasi Karakter Sensitif Gender dalam Kurikulum Pendidikan - Inayatul Ulya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Indonesia is one of countries which strongly struggle to reach Justice and Equality ofGender (KKG). This article aims to describe the internalization of gender in theeducation curriculum. The research method used in this study is library Research method by collecting some data from relevant sources such as books, and articles related to the main discussion. The research result shows that based on the Presidential Instruction No. 9 of 2000, the government has given an instruction to apply gender mainstreaming into all aspects of development including educational development. In this case, it is necessary to design a gender based curriculum which integrates gender into education curriculum through the school management, learning process, students’ activity, as well as school culture.